Risk Perceptions, Self-Efficacy, Response Efficacy and Premarital Intimacy Behavior among Adolescents: A PLS-Sem Approach - Erni Gustina; Yuniar Wardani; Liena Sofiana; Suci Musvita Ayu; Kania Valentia Febriana; Ardyawati Wira Oktaviana; Baiq Qatrunnada Hariyanti (Universitas Ahmad Dahlan, 2026)
Premarital intimacy behavior among adolescents is a significant reproductive health concern, however, the cognitive pathways linking risk perception to such behavior are not yet fully understood. This cross-sectional study, conducted in schools within Bantul District, Yogyakarta (n=288), examined the correlations among perceived severity, perceived vulnerability, response effectiveness, self-efficacy, and premarital intimacy behavior using PLS-SEM. The outcome was operationalized using indicators of mild affectionate/intimacy behaviors, rather than sexual intercourse or broader sexual risk behaviors. Structural findings show that severity markedly enhances response efficacy (β=0.480; T-Value=5.870) and self-efficacy (β=0.407; T-Value=3.460), whereas vulnerability similarly elevates response efficacy (β=0.285; T-Value=3.456) and self-efficacy (β=0.337; T-Value=3.149). These findings suggest that risk perception operates indirectly through self-efficacy and response efficacy; however, risk perception was associated with higher response efficacy and self-efficacy, which in turn decreases adolescent premarital intimacy behavior. Increasing self-efficacy is crucial for understanding and reducing premarital intimacy behavior among adolescents in educational settings. A more adaptive, empowering, and sustainable sex education program is expected to improve risk perception and self-efficacy, thereby reducing premarital intimacy behavior among adolescents.